Determination of MIC Distribution of Arbekacin, Cefminox, Fosfomycin, Biapenem and Other Antibiotics against Gram-Negative Clinical Isolates in South India: A Prospective Study - Rajenderan, Sangeetha; Balaji, Veeraraghavan; Anandan, Shalini; Sahni, Rani Diana; Tansarli, Giannoula S.; Falagas, Matthew E. (PLOS ONE, 2014)
Objectives To determine the in vitro activity of antibiotics, including arbekacin, cefminox, fosfomycin and biapenem which are all still unavailable in India, against Gram-negative clinical isolates. Methods We prospectively collected and tested all consecutive isolates of Escherichia coli, Klebsiella spp., Pseudomonas aeruginosa and Acinetobacter spp. from blood, urine and sputum samples between March and November 2012. The minimum inhibition concentration (MIC) of 16 antibiotics was determined by the broth micro-dilution method. Results Overall 925 isolates were included; 211 E. coli, 207 Klebsiella spp., 153 P. aeruginosa, and 354 Acinetobacter spp. The MIC50 and MIC90 were high for cefminox, biapenem and arbekacin for all pathogens but interpretative criteria were not available. The MIC50 was categorized as susceptible for a couple of antibiotics, including piperacillin/tazobactam, carbapenems and amikacin, for E. coli, Klebsiella spp. and P. aeruginosa. However, for Acinetobacter spp., the MIC50 was categorized as susceptible only for colistin. On the other hand, fosfomycin was the only antibiotic that inhibited 90% of E. coli and Klebsiella spp. isolates, while 90% of P. aeruginosa isolates were inhibited only by colistin. Finally, 90% of Acinetobacter spp. isolates were not inhibited by any antibiotic tested. Conclusion Fosfomycin and colistin might be promising antibiotics for the treatment of infections due to E. coli or Klebsiella spp. and P. aeruginosa, respectively, in India; however, clinical trials should first corroborate the in vitro findings. The activity of tigecycline should be evaluated, as this is commonly used as last-resort option for the treatment of multidrug-resistant Acinetobacter infections.